Мотив і його складники : проблема побудови структурно-семантичної моделі - Тимченко, А.О. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2009)
The article deals with a motif as a theoretical problem. The definition of a motif and its main features are determined. The question of creating of the structural-semantic model of a motif is raised. The trichotomy model is proposed. It includes such components as the nucleus (the symbolic and archetypical information), the body of the motif (its display in the concrete work of art) and the motif's field (the totality of the details and the images, which are caused by the emergence of the motif). The conclusion is made that the trichotomy structural-semantic model of a motif can be used in a motif analysis of the writings.
У статті йдеться про мотив як теоретичну проблему; провідним завданням дослідження є побудова структурно-семантичної моделі мотиву. Пропонується створення трихотомічної моделі, складниками якої будуть ядро (містить архетипну, символьну інформацію), тіло (вияв у конкретному творі) та мотивне поле (сума образів, деталей, що актуалізуються наявністю мотиву в тканині твору). Робиться висновок про продуктивність цієї моделі, потребу в дослідженні її функціонування та можливість її використання на практиці.
Keywords: мотив; модель; структурно-семантичний; дихотомія; трихотомія